Genome mining reveals chitin degradation potential of \(Streptomyces parvulus\) VCCM 22513 - Ngoc Tung, Quach; Thu An, Nguyen Thi; Hanh Nguyen, Vu Thi; Quyet Tien, Phi (Academia Journal of Biology, 2023)
The genus Streptomyces is not only known as a natural producer of antibiotics but also a prolific source of chitinolytic enzymes that digest recalcitrant chitin to chitooligosaccharides. However, only a few reports have used whole-genome sequencing to study chitin degradation of Streptomyces to date. In the present study, out of 22 Streptomyces strains, Streptomyces parvulus VCCM 22513 produced the highest chitinase activity. Time courses of incubation revealed that the maximum chitinase (0.91 ± 0.04 U/mL) of this strain was observed after 96 hours in the yeast extract salts medium supplemented with 10.0 g/L colloidal chitin. Additional genomic analysis of VCCM 22513 was also conducted to discover the genomic information related to chitin degradation. The VCCM 22513 genome consists of 341 CAZy genes divided into 6 families including glycoside hydrolase (134 genes), carbohydrate-binding module (88 genes), glycosyl transferase (87 genes), carbohydrate esterase (18 genes), polysaccharide lyase (7 genes), and auxiliary activity (7 genes). Further genome mining revealed the presence of 10 chitinases, 4 lytic polysaccharide monooxygenases, and 14 β-N-acetylhexosaminidases, which mainly contribute to the degradation of chitin polymers. This is the first report revealing the mechanism underlying the chitin degradation of S. parvulus. Further investigations are required to characterize chitinolytic enzymes found in this study for the bioeconomic production of high-quality chitooligosaccharides from chitin food wastes.